Overview of arthropods & their impact on the health of humans & other vertebrates 2 - Romoser, William S. (Henry Stewart Talks, 2010)
Both mandibulate and chelicerate arthropods can impact human and animal health, The most problematic mandibulates are insects, including cockroaches, lice, blood-feeding true bugs, fleas, true flies, ants, bees, and wasps, Among the chelicerates, mites & ticks, spiders and scorpions are of importance, Mites and ticks as vectors (transmitters) of pathogens and pests, Spiders and scorpions as venomous biters and stingers